Youth vision 2020 towards building an India of our choice - Satapathy, Sachidananda (ed.) (New Delhi, 2007)
The whole book is a compilation of more than forty insightful papers written by young people of this country and supplemented by people of eminence. All have drawn a line map regarding how to go about from this point to the development of this country. As young people of today are the sensible citizens of tomorrow, it has become necessary to conceptualise such project of Youth Vision 2020, giving them voice and make their participation strong in nation building process. This project will certainly inspire other youngsters whose role the country need in its development process. The country needs badly young people's involvement in its day-to-day affairs, which is lacking till date and their apathetic attitude to any burning issue is making our country weak. This project helped many bright young people to think deeply their country and their people and above all future and at least gather some dream to realize. The ideas gathered in the book are incredible and if practised can make this country a place, where everybody can have a choice of their own. The book is a must reading for all development practioners, political leaders, students, academicians, and above all, anybody having some sense, deep concern and empathy for India's progress.
Keywords: Economic development-India